1992
DOI: 10.1093/ije/21.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Preterm and Term Low Birthweight in Ahmedabad, India

Abstract: To identify and quantify risk factors for preterm and term low birthweight (LBW) we conducted a hospital-based case-control study, linked with a population survey in Ahmedabad, India. The case-control study of 673 term LBW, 644 preterm LBW cases and 1465 controls showed that low maternal weight, poor obstetric history, lack of antenatal care, clinical anaemia and hypertension were significant independent risk factors for both term and preterm LBW. Short interpregnancy interval was associated with an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
79
2
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 0 publications
34
79
2
7
Order By: Relevance
“…22 Our study showed Muslim mothers had more lbw babies might be due to some cultural factors might have played some negative birth effects and it was in contrast to the findings shown by Mavalankar DV et all in Ahmedabad, India where they found Muslim women were at much lower risk of lbw babies than Hindu mothers. 23 Similar to other studies, this study also found more proportion lbw were among illiterate and primarily educated mothers. 3,21,24,25 Reason cited behind this might be, lower level education might have associated with lower health awareness and health seeking behavior of the mothers.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…22 Our study showed Muslim mothers had more lbw babies might be due to some cultural factors might have played some negative birth effects and it was in contrast to the findings shown by Mavalankar DV et all in Ahmedabad, India where they found Muslim women were at much lower risk of lbw babies than Hindu mothers. 23 Similar to other studies, this study also found more proportion lbw were among illiterate and primarily educated mothers. 3,21,24,25 Reason cited behind this might be, lower level education might have associated with lower health awareness and health seeking behavior of the mothers.…”
Section: Discussionsupporting
confidence: 90%
“…),no.of antenatal visits ≥ 4,consumed extra diet & extra meal and Iron & Folic acid tablets ≥ 100,daily sleep & rest ≥ 10 hrs., taken 2 doses of Tetanus Toxoid, Institutional delivery had significantly lesser proportion of lbw babies. 3,15,16,19,21,23,24 We found that girls were more likely to be LBW infants than boys is in accordance with other study. 21 Mothers had regular bathing or brushing had more lbw babies, reason of which could not be explained.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Saúde Pública, Rio de Janeiro, 16(1):83-94, jan-mar, 2000 Introdução Apesar dos avanços alcançados pelos programas de investigação sobre os fatores de risco da prematuridade, a maioria dos nascimentos prematuros ainda não tem fisiopatogênese conhecida (Kramer, 1987;Kramer et al, 1988;Mavalankar et al, 1992;Fortier et al, 1995;Hedegaard et al, 1996;Lang et al, 1996). Dentre as principais dificuldades dessa linha de pesquisa, destaca-se a falta de consenso com relação aos indicadores e medidas usados para aferir alguns de seus potenciais fatores de risco e à estratégia padrão utilizada para seu diagnósti-co (Dunn, 1985;Henriksen et al, 1995).…”
Section: Artigo Articleunclassified